2010
DOI: 10.1149/1.3484672
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Solid Alkaline Fuel Cells Employing Layered Perovskite-Type Oxides as Electrolyte

Abstract: This hypothesis suggests that the possibility of a new alkaline fuel cell by using layered perovskite as electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In our previous study, we reported that the five kinds of layered perovskite oxides (LaSr 3 Fe 3 O 10 , NaLaTiO 4 , Sr 4 Co 1.6 Ti 1.4 O 8 (OH) 2 •xH 2 O, RbLaNb 2 O 7 and LaFeO 3 ) showed electrochemical performance as electrolyte for alkaline fuel cell without cathode catalyst (6). The results conformed to characteristic property of AFC.…”
Section: Introductionsupporting
confidence: 54%
“…In our previous study, we reported that the five kinds of layered perovskite oxides (LaSr 3 Fe 3 O 10 , NaLaTiO 4 , Sr 4 Co 1.6 Ti 1.4 O 8 (OH) 2 •xH 2 O, RbLaNb 2 O 7 and LaFeO 3 ) showed electrochemical performance as electrolyte for alkaline fuel cell without cathode catalyst (6). The results conformed to characteristic property of AFC.…”
Section: Introductionsupporting
confidence: 54%
“…LaSr 3 Fe 3 ­O 10–2 x ­(OH) 2 x ·H 2 O functions as an electrolyte for OH – conduction . It has recently been reported that an inorganic oxide containing OH – functioned as an anion conductor. RP-LaSr 3 Fe 3 O 10 without intercalation of water with high electrical conductivity functions as a catalyst for oxygen reduction reaction, since the fuel cell showed completely theoretical voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging as another promising alternative in layered perovskites, the Ruddlesden–Popper (RP)-type perovskite (A n +1 B n O 3 n +1 ), especially when n = 3 (e.g., La 4 Ni 3 O 10 , Sr 3 NdFe 3 O 10 , and Sr 4 Co 1.6 Ti 1.4 FeO 8 (OH) 2 · x H 2 O), has received increasing attention in the fields of oxygen permeation and solid oxide fuel cell owing to its large oxygen nonstoichiometry without undergoing phase transition. As a typical RP-type perovskite, the Sr 4 Fe 3 O 10 ( n = 3) consisting of three layers of SrO–FeO 2 –SrO coupled with a rock salt layer of SrO along the c axis is an attractive candidate because of its structural stability, high conductivity, and tunable doping property. Moreover, a partial substitution of La for Sr at the A-site (i.e., LaSr 3 Fe 3 O 10 ) could further stabilize the intergrowth structure and simultaneously adopt substantial oxygen vacancy without forming a secondary phase and degrading the structural stability .…”
Section: Introductionmentioning
confidence: 99%